The effect of self-efficacy, organizational culture and work motivation on employee performance at the department of education and culture of lampung province - Dhiya Alifya; Nova Mardiana (Asian Journal of Economics and Business Management, 2022)
This study aims to determine the effect of self-efficacy, organizational culture and work motivation on employee performance at the Education and Culture Office of Lampung Province. The type of research used in this research is quantitative research. The sampling technique used is probability sampling with the Simple Random sampling method for as many as 168 employees. The analytical tool used is multiple linear regression analysis using IBM SPSS version 25 software. The results of this study support the hypothesis that self-efficacy, organizational culture, and work motivation have a positive and significant effect on employee performance at the Lampung Province Education and Culture Office. Suggestions for the Education and Culture Office of Lampung Province to pay more attention to the problems faced by employees, such as how to manage stress levels and handle unexpected events. Organizations are also expected to pay more attention to employee penalties or sanctions if performance is not good and to reward employees who excel. Next, pay attention to employees' qualifications and the existing food facilities in the organization's environment. Employees are also expected to stay focused and work-oriented by reducing talking to coworkers about negative aspects of the workplace.